Persuasion in Self-improvement Books - Koay, Jeremy (Postdisciplinary Studies in Discourse, 2019)
'Positioned at the interface between ideology, discourse and text, Jeremy Koay's exploration of self-improvement books provides a scholarly examination of the genre, scrutinising both the communicative intentions and textual means used by its writers.' -Ian Bruce, Senior Lecturer, University of Waikato, New Zealand 'In his book, Koay provides theoretically well-grounded inside view of self-improvement books based on both substantial and thoughtful analyses. A fascinating read.' -Brian Paltridge, Professor of TESOL, University of Sydney, Australia This book investigates how persuasion relates to values in self-improvement literature, revealing the discursive practices used to persuade and engage their readers, and construct a credible persona. The author adopts a corpus-driven approach that encompasses an examination of genre analysis and linguistic features such as narrative, pronoun, grammarand structure. The book further draws on insights from original interviews with writers and readers of self-improvement books, as well as people who do not read the genre. It begins by providing a helpful overview of the concepts of ideology and genre. A brief history of self-improvement books and their values and assumptions provide the context for the analysis. Where relevant, linguistic features in self-improvement books are compared with other genres (e.g. academic text, conversation, news). This book will be of interest to students and scholars in the fields of linguistics, culture and media studies. Jeremy Koay is a New Zealand-based independent researcher and an education consultant at EduMaxi. His research interests include discourse analysis, English for specific purposes, genre studies, functional linguistics and applied linguistics.